Autonomia docente no novo ensino médio: possibilidades e constrangimentos no contexto do RS - Centa, Fernanda Gall (2022)
This research project was developed from studies carried out within the scope of the Study, Research and Interventions Group “Educational Innovation, Educational Practices and Teacher Training” (INOVAEDUC) and is linked to the Umbrella Project under number 045936 “Needs for Teaching Work in Public Schools for Effective Permanence and Qualified Learning of High School Students in Brazil (NETRADOCEM)”.Teacher autonomy is a complex process, seen as an important aspect in the quality of education. To have autonomy is to make the professional develop qualities in the educational practice. Teacher Autonomy is seen as a quality of the educational phenomenon that does not apply only to professional quality, it consists of awareness of teaching, of doing and being a teacher, of the meaning of teaching and education in society. Only in this way will it be possible to achieve the real concept of “professional autonomy”. We emphasize that, in order to be successful and successful in school education, we must invest in professional autonomy, prestige, respect and trust in teaching work, in addition to working conditions and an adequate professional environment. It is noteworthy that it is not possible to separate teaching autonomy from curricular reforms. The recent reform of the New High School, arising from Law 13,415 of 2017, proposes numerous changes to this level of education. Such changes will only have positive effects if actions such as the restructuring of curricula, based on the prescriptions and guidelines present in the text of the National Common Curricular Base (BNCC), have their impasses resolved. Thus, the interest of our research also emerged from the extension actions developed by the INOVAEDUC Group, in which it was possible to perceive, in the speeches of high school teachers, concerns related to their autonomy in the face of the guidelines arising from legal regulations. It is at this point that our research is situated, the Law of High School Reform, in the context of the practice and the perception of the subjects - the teachers - about their autonomy, their subjectivity - about the texts, the way of reading and translating these texts, the ways they conceive and appropriate them and the proposed guidelines, the reinterpretation processes that they carry out and that affect the production of meanings. We take as the focus of this research the “Teacher Autonomy in the Implementation of the New High School”. From it, we aim to understand the possible ways in which teacher autonomy develops in the process of changing the curriculum in the implementation of the New High School. To guide the development of this research in the perspective of achieving this objective, we established the following research problem: What relationships can be established between teacher autonomy and curricular changes in the context of the implementation of the New High School in schools of the Public School Network of RS maintained by the 8th CRE/SEDUC/RS? To answer this problem, we will carry out an empirical research of a qualitative nature. For this, we will use two sources for the collection of information (1) Subjects: teachers working in pilot high schools of the State Public School Network of RS; (2) members of the pedagogical coordination team working in the pilot high schools of the State Public School Network of RS, in the region of 8th CRE/SEDUC/RS, RS. As instruments for collecting information, we intend to carry out interviews with these teachers and coordinators. For the organization and treatment of the information collected, we will use the basic guidelines of the so-called "Grounded Theory”. The study made it possible to relate the movements carried out by the pilot schools in the face of the ways that teacher autonomy develops in elements such as strategies, actions and decisions. In the relationship between teacher autonomy and curricular changes in the NEM implementation process, we list some aspects: the relationship between teacher autonomy and the lack of specific guidelines and training; teaching autonomy and school organization of an organizational and pedagogical nature; teacher autonomy and the Reference Matrix teacher autonomy and the reduction of workload; teaching autonomy and the difficulties of pedagogical didactic planning; teaching autonomy in the difficulties of school schedules; teaching autonomy in the difficulty of elaboration and understanding.